Democratic Republic of the Congo : Enhanced Initiative for Heavily Indebted Poor Countries; Completion Point Document and Multilateral Debt Relief Initiative Paper. (IMF Staff Country Reports; Country Report ;, 2010)
The Democratic Republic of the Congo (DRC) has successfully implemented key reforms under the enhanced Heavily Indebted Poor Countries (HIPC) Initiative, despite experiencing exceptional challenges since the decision point, including a challenging security situation. Revised present value of HIPC assistance has given satisfactory assurances of their participation in the enhanced HIPC Initiative. The DRC does not qualify for topping-up under the enhanced HIPC Initiative. Full delivery of HIPC debt relief, and additional bilateral assistance beyond HIPC and Multilateral Debt Relief Initiative debt relief at the completion point would reduce the DRC's external debt burden significantly.